Pakistan Rural Household Panel Survey (PRHPS) 2014, Round 3 - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
The Pakistan Rural Household Panel Survey (PRHPS) 2014, Round 3 is the third round of the PRHPS; Round 1 and 2 were conducted in 2012 and 2013 respectively. This survey aims to provide a quantitative basis to identify and address urgent economic development and policy priorities in Pakistan. Many modules and questions in Round 3 are consistent with the prior rounds. PRHPS Round 3 was able to collect complete data from 1,876 households in the rural areas of three provinces namely: (i) Punjab; (ii) Sindh; and (iii) Khyber Pakhtunkhwa (KPK).The sample is representative of the rural areas of Punjab and Sindh provinces, and of the rural areas in 11 of the districts in KPK province. The survey collected information on a large number of topics including sources of income, nature of employment, consumption patterns, time use, assets and savings, loans and credit, education, migration, women decision making, economic shocks, transfers in and out, health and nutrition, and participation in social safety nets. Four survey instruments were developed to collect this information. These included two household questionnaires (designed to collect individual- and household-level information from a main male and a main female respondent who were interviewed separately), a community questionnaire, and a price questionnaire.